Desert one [videorecording (DVD)] - Carter, Jimmy, 1924-; Mondale, Walter F., 1928-2021; Koppel, Ted, 1940 February 8- (Greenwich Entertainment, 2020)
It has been called 'the most audacious, difficult, complicated rescue mission ever attempted.' This account uniquely blends emotion and bravado to tell the incredible tale of America's secret mission to free the hostages of the 1979 Iranian Revolution.